2014
DOI: 10.3747/pdi.2012.00293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Break-In Period on the Short-Term Outcomes of Patients Started on Peritoneal Dialysis

Abstract: ♦ Objectives: Peritoneal dialysis (PD) is one of the firstline modalities of renal replacement therapy in patients with end-stage renal disease. Guidelines recommended a break-in period of at least 2 weeks before full PD start. However, the optimal duration of the break-in period is still unclear. In the present study, we investigated the effect of various break-in periods on short-term outcomes in patients on PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 26 publications
7
76
0
3
Order By: Relevance
“…This has recently been confirmed in a much larger Chinese study (9) including 657 patients divided into 3 groups according to the length of the break-in period (≤ 7 days, 8 -14 days, and > 14 days) between catheter implantation and initiation of PD. They reported that the group with a break-in period ≤ 7 days had a statistically significantly higher incidence of mechanical complications compared with the group with a break-in period > 14 days during the first 6 months of PD.…”
Section: Complicationsmentioning
confidence: 56%
“…This has recently been confirmed in a much larger Chinese study (9) including 657 patients divided into 3 groups according to the length of the break-in period (≤ 7 days, 8 -14 days, and > 14 days) between catheter implantation and initiation of PD. They reported that the group with a break-in period ≤ 7 days had a statistically significantly higher incidence of mechanical complications compared with the group with a break-in period > 14 days during the first 6 months of PD.…”
Section: Complicationsmentioning
confidence: 56%
“…Ivarsen and Povlsen [1], Povlsen et al [8] and Liu et al [16] showed that total mechanical complications occurred significantly more in urgent-start than conventional start PD [1,8,16]. They noted that there was an increased need for surgical replacement of PD catheter in the urgent group.…”
Section: Discussionmentioning
confidence: 99%
“…Seven previous studies assessed the risk of catheter dysfunction in urgent-start PD [1,4,5,6,7,10,16] and the rate of risk ranged from 1.9 to 33.3%. These studies also assessed the rate of PD-related infections.…”
Section: Discussionmentioning
confidence: 99%
“…A previous large, retrospective study at this center including 657 ESRD patients, of whom 136 (20.7%) had diabetes, found that a break-in period of < 1 week might be related to a minor increased risk of mechanical complications but had no major effect on technique survival in PD patients [21]. Another previous large, retrospective study (n = 178, including 51 diabetics) in our center reported that urgent-start PD resulted in fewer short-term dialysis-related complications, fewer dialysis-related complications requiring re-insertion, and less bacteremia compared with urgent-start HD, with no significant difference in patient survival [22].…”
Section: Discussionmentioning
confidence: 99%